PERENCANAAN DAN PENGELOLAAN KEUANGAN SEDERHANA BERBASIS TEKNOLOGI PADA SISWA/I SMK KARYA NASIONAL, KAB. KUNINGAN JAWA BARAT - Yopy Ratna Dewanti; Faridha Nurazizah Yasirrahayu; Sari Mujiani; Moh. Abdurrasyid; Istna Fibriyadi (JURNAL ABDIMAS PLJ, 2024)
The Digital era is a time where everyone can communicate with each other very closely, even though they are far apart. We can find out certain information very quickly, even in real time. Globalization is a process of international integration that occurs as a resul of the exchange of world views, product, ideas and other cultural aspects caused by the development of telecomunications, transportation and internet infrastructure. In financial management, both recording income and expenditure is very important as a basis for evaluating existing business systems.wtih the development of increasingly better technology, it is necessary to have a touch of computerized technology in financial management in recording income and expenditure transactionsso that it will be faster and more effective in recording transactions. The method used in this service is a socialization method regarding the use of information in financial management and s followed by training and practice in preparing information technology-based financial reports. As a result of this service, it is hoped that students will have the ability to prepare technology-basaed financial reports and able to record transaction using computer application. It is also hoped that students can increase transparency and accountability in financial management when facing the world of work after graduating.